Southeast Asian paper tigers? : from miracle to debacle and beyond - Jomo K. S. (Jomo Kwame Sundaram) (RoutledgeCurzon studies in the growth economies of Asia ;, 2003)
This important collection is a timely contribution to the debate on the Asian financial crisis. With chapters by well-established international Asian economics experts, this book constitutes a finely judged example of the varying opinions.